Impact of Farmers' Cooperatives on Socio-economic Living Conditions of Rural Households in North of Burundi - Manirakiza, Dismas; Mulumeoderhwa, FidÃ¨le; Maniriho, Aristide; Ndimanya, Patrice; Lebailly, Philippe (International Journal of Economics and Financial Issues, 2019)
The study aimed to assess the farmers' cooperatives impact on the socio-economic living conditions of their members in North of Burundi. A research survey was conducted on two farmers' groups such as a sample of 90 farmers randomly chosen in three main cooperatives and a control sample of 60 non-members. Data were analyzed with a comparative approach of descriptive statistics. Among six main food crops considered by the study, results show a significant contribution of the cooperative only on bananas' production (p=0,075). Moreover, members gain a cost reduction of 50% per kg in maize milling or rice dehulling. Thanks to the multiple financial opportunities within the cooperative, members improve the quality of their houses (12%), subscribe supplementary health insurance (38%), pay easily the school fees for their children and equip themselves with household equipment. Finally, the value of solidarity among members enhances the spirit of confidence and cohesion in the community. Keywords: Farmers' cooperatives, impact, socio-economic living conditions, rural households JEL Classifications: O22, Q12, Q13 DOI: https://doi.org/10.32479/ijefi.8981